Defect of LSS Disrupts Lens Development in Cataractogenesis - Zhao, Minglei; Mei, Tingfang; Shang, Bizhi; Zou, Bin; Lian, Qing; Xu, Wenchang; Wu, Keling; Lai, Yuhua; Liu, Chujun; Wei, Lai; Zhu, Jie; Zhang, Kang; et al. (Frontiers in Cell and Developmental Biology, 2021)
Congenital cataract is one of the leading causes of blindness in children worldwide. About one third of congenital cataracts are caused by genetic defects. LSS, which encodes Lanosterol synthase, is a causal gene for congenital cataracts. LSS is critical in preventing abnormal protein aggregation of various cataract-causing mutant crystallins, however, its roles in lens development remains largely unknown. In our study, we generated a mouse model harboring Lss G589S mutation, which is homologous to cataract-causing G588S mutation in human LSS. LssG589S/G589S mice exhibited neonatal lethality at postal day 0 (P0), whereas these mice showed severe opacity in eye lens. Also, we found that cataract was formed at E17.5 after we examined the opacity of embryonic lens from E13.5-E18.5. Moreover, disrupted lens differentiation occurred at E14.5 prior to opacity of eye lens was formed, shown as delayed differentiation of lens secondary fiber and disordered lens fibers organization. In addition, RNA-seq analysis indicated that cholesterol synthesis signaling pathways were significantly downregulated. Overall, our findings provide clear evidence that a mouse model harboring a homozygous Lss G589S mutation can recapitulate human congenital cataract. Our study points out that LSS functions as a critical determinant of lens development, which will contribute to better understand LSS defects in cataractogenesis and develop therapies for cataract.